147 QRISK3 improves identification of endothelial dysfunction and cardiovascular disease risk in patients with systemic lupus erythematosus. (June 2018) - Edwards, N; Langford-Smith, AWW; Parker, B; Bruce, I; Reynolds, JA; Alexander, Yvonne; McCarthy, E; Wilkinson, FL
Abstract : Introduction: Systemic Lupus Erythematosus (SLE) is an inflammatory autoimmune condition associated with endothelial dysfunction, elevating the risk of cardiovascular disease 50-fold in young women. The QRISK2 algorithm is used currently to predict the 10 year cardiovascular risk in the UK population; however, an updated QRISK3 model was recently released, which considers inflammatory variables such as SLE and steroid prescription. This study aims to elucidate whether QRISK3 is more representative of endothelial dysfunction and cardiovascular risk in SLE patients and if novel biomarkers of SLE disease activity, including endothelial microvesicles (EMVs), correlate with increased risk. Methods: QRISK scores of SLE patients (n=109) and controls (n=29) were determined using clinical data. Potential markers of SLE-specific endothelial dysfunction were quantified in a smaller patient cohort (n=60) using flow cytometry and ELISA techniques and included; CD144 +EMVs, high sensitivity C-reactive protein (hsCRP) and triglycerides. Results: QRISK3 scores were significantly elevated in SLE patients (average 5.1%) compared to controls (0.3%; p<0.001), newly identifying 19% of patients as _x0018_high risk' (QRISK3 vs QRISK2: 30 vs 9; p<0.001). _x0018_Missed' high risk patients had increased likelihood of lupus nephritis, corticosteroid prescription and positive anti-cardiolipin antibody test compared to low risk patients. Levels of EMVS, hsCRP and triglycerides were significantly elevated in the missed group (p<0.05) whereas rates of antiplatelet (38.1%) and statin (23.8%) prescription were low. Conclusion: QRISK3 identifies significantly more SLE patients at high cardiovascular risk than QRISK2, and is associated with standard and novel markers of SLE-specific inflammation and endothelial dysfunction. The use of QRISK3 as a predictor of cardiovascular risk will support improved management of vascular health and assist in prevention of premature mortality in SLE patients.